The review of the monograph “Transport: Technologies, Economy, Environment, Health” - Jurkauskas, Habil A. (Transport, 2003)
From the first sight the improvement of transport technologies seems to be simple replacement of old transport means/vehicles by new ones. However, even if the most advanced transport means are purchased, they may be used absolutely inefficiently. Therefore, besides transport means it is necessary to improve the entire technological process of transportation. For this purpose many kinds of research have to be carried out, such as: the identification of freight and passenger flows, their constant monitoring and forecasting, the optimisation of the road network and transport flows in it, the optimisation of freight origin and distribution places, etc. Abroad there are many publications concerning the optimisation of long distance transport network and transportation of goods weighing 20–40 tons. However, actually there is no research of such cases when the weight of freight is 50–1500 kg and the transport network is in a small scale region, let us say in a town, under the conditions of congestion of the road network and ecological restrictions. It was attempted to propose certain solutions in this field: 1) the methodology of statistical analysis of freight flows and forecasting was proposed; 2) the problem of information storage is usually encountered in using statistical information on freight flows, for this purpose relevant algorithms for the solution of this problem are proposed.First Published Online: 19 Dec 2011